2021
DOI: 10.2355/isijinternational.isijint-2020-231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gas Pressure on the Formation Mechanism of Welds Based on Local Dry Underwater Welding

Abstract: During the local dry underwater welding process, the gas pressure in the micro drainage cover plays a key role in the formation of welds, but the relationship among the stability of the underwater arc, the formation of welds and the gas pressure has not been clarified. In this study, a micro drainage cover with dual-gas curtain based on the Lafar tube was used in the local dry underwater MIG welding experiments at a depth of 20 cm to explore the influence of gas pressure on the formation of underwater welds. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…This can be achieved by pushing the water away with a shielding gas using special nozzles so that a local cavity is created. Experiments have shown that a gas pressure of 0.2 MPa is needed for successful local cavity welding at a water depth of 20 cm ( Han et al, 2021 ). Since the surrounding pressure increases linearly with depth, it can be expected that the pressure needed for the draining gas also increases linearly.…”
Section: Manipulation and Maintenance Methodsmentioning
confidence: 99%
“…This can be achieved by pushing the water away with a shielding gas using special nozzles so that a local cavity is created. Experiments have shown that a gas pressure of 0.2 MPa is needed for successful local cavity welding at a water depth of 20 cm ( Han et al, 2021 ). Since the surrounding pressure increases linearly with depth, it can be expected that the pressure needed for the draining gas also increases linearly.…”
Section: Manipulation and Maintenance Methodsmentioning
confidence: 99%